Estrategias motivacionales para promover la participación activa en los estudiantes de La Unidad Educativa “Presidente Vicente Ramón Roca”, Tres Postes - Nieto Mayorga, Juan Miguel (2024)
This work aims to propose motivational strategies to promote active participation in students, for this, it began with a diagnosis of the characteristics of active participation, the strategies used by teachers were identified. The methodology used initially served to select pertinent information about the teaching strategies that consist of planning classes with different teaching activities and with duly established procedures, so that students obtain a genuine interest in learning the contents and feel motivated to participate. actively in the learning process individually and collaboratively. In another aspect, the survey was used as a research tool, this was applied to 133 subjects, which allowed testing the hypothesis that reached a result of 0.000 < 0.05, and thus accepting the hypothesis to reach the conclusions that the strategies Motivational motivations used by teachers are scarce, most omit them and others apply them without previously planning them, however, they agree that the application of gamification, through the Educaplay web tool, is a very good alternative, because it motivates the teacher to create activities so that their students can develop them in a dynamic and interactive way, accompanied by the respective monitoring and timely feedback from the class. It was also determined that with the use of the Educaplay virtual strategy, students are motivated to investigate, recognize and develop the activity with interest and enthusiasm, which strengthens the active participation of students.